The workload-indexed blood pressure response predicts cardiovascular events and all-cause mortality in coronary artery disease. (3rd October 2022) - Braganca, B; Oliveira, I; Cruz, I; Lopes, R G; Queiros, C; Pinto, P; Andrade, A
Abstract: Background: Abnormal blood arterial pressure response to exercise (BPR) is a cardiovascular (CV) risk factor (CVRF). The concept of pathological BPR, believed to be an excessive raise or decrease, has been challenged. The workload-indexed blood pressure response (WBPR) recently emerged in an attempt to normalize hypertensive responses to exercise. However, it remains to be explored its value in high-risk CV subjects. Purpose: Evaluation of the predictive value of WBPR in the occurrence of CV events and death in coronary artery disease (CAD) patients. Methods: A cohort of 318 patients with known CAD, who underwent Bruce protocol treadmill testing between 2009–2010, were retrospectively followed to 11/2021 (9.9±2.3 years) to assess the predictive value of WBPR for the occurrence of death and CV events. The WBPR is the ratio between systolic blood pressure variation from rest to peak exercise (ΔSBP) and metabolic equivalent of task (MET-1). High and low WBPR groups were created based on median value for this sample (5.2 mmHg/MET). Data presented: mean ± standard deviation; 95% confidence interval (CI) for hazard ratios (HR); significance between groups p<0.05. Results: Low vs high WBPR groups were similar at baseline for sex (88% male, p=0.67), hypertension (63%, p=0.18), diabetes (32%, p=0.34); dyslipidemia (72%, p=0.62), myocardial infarction (75%, p=0.39) and heart failure (HF) (9.9%, p=0.07), with exception for overweight/obesity (90% vs 82%, p=0.009) and age (57±11 vs 61±8 years, p=0.009) that were higher in the high-WBPR group. No significant differences were found between groups for medication at baseline, including anti-hypertensive, anti-thrombotic or anti-ischemic drugs. In the follow-up period occurred 43 deaths (12 CV deaths), 58 reinfarctions, 94 worsening/de novo HF and 29 strokes. A non-linear J-shaped relationship was observed between WBPR and most events. In the event-free survival analyses using Cox regression, the high-WBPR group was associated with all death (HR 2.0 (CI 1.0–3.9, p=0.042), reinfarction (HR 2.3 (CI 1.2–4.1, p=0.008), and worsening/de novo HF (HR 1.7 (CI 1.0–2.9, p=0.043) after adjusting for baseline age, CVRFs and medication. In receiver operating characteristic curves, adding WBPR to a model with other cardiac stress variables (double product, ST-T changes, symptoms, and test positivity) significantly improved the power to predict all death, with an area under curve of 0.73 (CI 0.66–0.80, p=0.037). Conclusions: Data shows that WBPR is a powerful independent predictor of future cardiovascular events and deaths in CAD patients. This highlights cardiac exercise stress testing as an important risk assessment tool in secondary prevention of cardiovascular disease. Funding Acknowledgement: Type of funding sources: None.